Regress as a Change of Community Law on Games and Their Effect on Property Ownership - Arianti, Farida; Fikri, M. Ihsanul; Rahmi, Zikra (TAWAZUN: Journal of Sharia Economic Law, 2023)
There has been a change in Islamic law in interpreting game play in society when the Eid celebration takes place and has made it a tradition. Changes in the law in the form of ignoring the rules of Islamic law regarding qimar (gambling). The purpose of this study is to explore how the process of partial abandonment of Islamic law is related to the implementation of the tasks of the community subsystem, namely Islamic economics and explore its influence on the abandonment of Islamic law. The method used is qualitative with a case study approach. Sources of data by looking at the social situation about the game to the point of boredom, data collection techniques through in-depth interviews with interview guides addressed to informants in the form of contract actors, as well as religious leaders, in addition to observation and analysis using qualitative descriptive analysis. The results of the study explain that first; The community plays games as a means of enlivening the Eid celebration every year in one village, in addition to being a means of property ownership for the community in a village. Second, there is a partial regress, especially in the form of disclaiming Islamic economic rules, so that the function of Islamic law as a comprehensive social control cannot be achieved.  The implication of this research is the view of betting-style game play and then being raffle  into a new and cultivated habit.